Effect of K/Al Molar Ratio on the Thermo-Mechanical Properties of Metakaolinite-Based Geopolymer Composites - Jan Kohout (MDPI AG, 2021)
A metakaolinite-based geopolymer binder was prepared by using calcined claystone as the main raw material and potassium as the alkaline activator. Chamotte was added (65 vol%) to form geopolymer composites. Potassium hydroxide (KOH) was used to adjust the molar ratio of K/Al and the effect of K/Al on thermo-mechanical properties of geopolymer composites was investigated. This study aimed to analyze the effect of K/Al ratio and exposure to high temperatures (up to 1200 °C) on the compressive and flexural strengths, phase composition, pore size distribution, and thermal dilatation. With an increasing K/Al ratio, the crystallization temperature of the new phases (leucite and kalsilite) decreased. Increasing content of K/Al led to a decline in the onset temperature of the major shrinkage. The average pore size slightly increased with increasing K/Al ratio at laboratory temperature. Mechanical properties of geopolymer composites showed degradation with the increase of the K/Al ratio. The exception was the local maximum at a K/Al ratio equal to one. The results showed that the compressive strength decreases with increasing temperature. For thermal applications above 600 °C, it is better to use samples with lower K/Al ratios (0.55 or 0.70).